Structural diversity of G-rich DNA : from telomeric G-quadruplexes to G-junction motifs - Lim, Kah Wai (2014)
Four-stranded G-quadruplex DNA have been implicated in cellular processes and shown to exhibit important functional properties. In particular, putative quadruplex motifs were identified in important genomic loci including telomeres and oncogenic promoters, rendering them promising therapeutic targets. G-quadruplex DNA could adopt diverse topologies, but current knowledge regarding their folding principles remains lacking. This study addresses the conformational heterogeneity of G-quadruplexes from human telomeric and promoter regions through the structural and biophysical characterization on a number of such sequences. In addition, the connectivity of duplex and quadruplex DNA is validated across the diverse geometries of the quadruplex, accompanied by a search for the existence of sequence motifs comprising both duplex and quadruplex elements in the human genome. These findings provide structural insights which could be useful towards the rational design of chemical ligands for therapeutic targeting of genomic G-rich sequences, and pave way for implementation of quadruplex motifs in DNA nanotechnology.